1991
DOI: 10.1177/0148607191015005513
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Central Venous Catheter‐Related Vascular Erosions

Abstract: Risk factors for superior vena cava perforations following central venous catheterization for total parenteral nutrition were identified in a retrospective study of 1058 catheters in 853 patients; 540 of these catheters were size 16-gauge (51%) and 518 size 14-gauge (49%). Of the size 14-gauge catheters, 274 (53%) were right-sided and 244 (47%) were left-sided subclavian catheters. Four patients (0.4%) had superior vena cava perforation. All had left-sided large bore 14-gauge catheters. All patients experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
3

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 15 publications
0
45
0
3
Order By: Relevance
“…It is difficult to estimate the incidence of pleural effusions originating from incorrectly inserted catheters since various factors may contribute. MUKAU et al [11] studied complications of 1,058 superior vena cava catheter procedures in 853 patients. All patients who developed pleural effusions had left-sided, large-bore 14G catheters (0.4%).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to estimate the incidence of pleural effusions originating from incorrectly inserted catheters since various factors may contribute. MUKAU et al [11] studied complications of 1,058 superior vena cava catheter procedures in 853 patients. All patients who developed pleural effusions had left-sided, large-bore 14G catheters (0.4%).…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review of more than 1,000 catheter placements, Mukau et al 10 reported four patients with perforation of the SVC. All four had left-sided catheters and the average time interval to clinical symptoms was 5 days.…”
Section: Catheter Tipmentioning
confidence: 99%
“…Some materials such as Teflon ® or polyethylene are well known thrombogenic compounds, whereas catheters made of silicone are safer, biologically inert and more resistant to thrombosis [15]- [17]. Each catheter is designated by the vessel and the place in which its distal extremity is located, that is, peripheral or central; by the permanence time (temporary, short term, long term or permanent); by its insertion localization (subclavian vein, femoral vein, internal jugular vein, basilic and femoral peripheral veins); as well as peripheral insertion central catheters-PICC.…”
Section: Introductionmentioning
confidence: 99%